Application of Communication in the General Field to Improve the Clean River Program Service in the Public Works and Housing Agency of Denpasar City - I Putu Anjaya Putra; I Gede Wirata; I Kadek Dede Junaedy (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This research discusses the implementation of communication in the General Sector of the PUPR Department of Denpasar City in the Clean River Program and the obstacles faced. The research was conducted using a qualitative approach through interviews. The results show that communication involves planning the placement of human resources according to the organizational structure, the use of information technology, and the active participation of human resources, although their abilities still need to be improved. Internal obstacles include complicated bureaucracy, inadequate officer skills, and unplanned employee transfers. External obstacles include technological limitations, use of technical language, and low public understanding of the importance of clean rivers.  To overcome these obstacles, it is recommended that training and technical guidance be carried out for employees, optimizing the use of technology, transparency of information, and simplifying bureaucratic communication. This is expected to increase the effectiveness of organizational communication and the smooth running of program services.